Decision Analysis Model Comparing Cost of IsoPSA™ vs Repeat Biopsy for Detection of Clinically Significant Prostate Cancer in Men with Previous Negative Findings on Biopsy. Issue 1 (20th January 2021) - Lotan, Yair; Stovsky, Mark; Rochelle, Robert; Klein, Eric
Abstract: Introduction: We compared cost of IsoPSA™ vs repeat biopsy in detection of clinically significant prostate cancer in men with previous negative office based prostate biopsy. Methods: A decision tree model compared cost of biopsy for all men with previous negative biopsy and rising prostate specific antigen (standard arm) vs initial IsoPSA with biopsies performed only in cases of abnormal IsoPSA. Study endpoints were cost, number of biopsies and cancers detected. Cost was based on Medicare reimbursement and peer reviewed literature. Cost of sepsis, complications and loss of work were incorporated into the analysis. Sensitivity analyses were performed varying model assumptions. A separate analysis incorporated cost of treatment for patients with cancer. Results: Using the baseline model with 20.5% prostate cancer incidence yielded an overall cost for 100 men of 197, 700 and 165, 300 for the standard and IsoPSA arms, respectively, including the cost of the IsoPSA assay, herein assumed to be 350. The IsoPSA arm detected 0.8 fewer Gleason 7–10 prostate cancers (12.6 vs 13.4) but generated 34% fewer biopsies. The IsoPSA arm was less expensive if overall biopsy cost is more than 1, 027, if IsoPSA cost is less than 674 or cancer rate was less than 70%. In the model incorporating treatment of men with a cancer diagnosis the IsoPSA arm was also less expensive, generating savings of 53, 300 per 100 men. Conclusions: The use of IsoPSA to select patients for repeat biopsy reduced the number of biopsies needed by 34% and generated significant cost savings.